Fermentative reforming of crude glycerol to 1, 3-propanediol using Clostridium butyricum strain L4. (April 2022) - Gupta, Pragya; Kumar, Manoj; Gupta, Ravi Prakash; Puri, Suresh Kumar; Ramakumar, S.S.V.
Abstract: Repurposed used cooking oil is a sustainable alternative to other feedstocks for biodiesel production offering enviro-economic benefits. Residual crude glycerol (RCG) from such biodiesel production plants is difficult to utilize due to presence of numerous toxic impurities with various inhibitory effects on biological fermentative reforming process. However, it is a new industrial feedstock for bio-based production of 1, 3-propanediol. In this work, a new Clostridium butyricum strain L4 was isolated from biogas reactor leachate after rigorous adaption and 35 subcultures under increasing stress conditions and studied for green production of 1, 3-propanediol (PDO) from RCG and further process development. Evaluation of fermentative reforming kinetics was performed and the optimal reaction conditions are pH 7.0, temperature 30 °C, 2 g yeast extract/L and 15 g ammonium sulphate/L. Glycerol-glucose co-fermentation (10:1) enhanced cell growth and thus, PDO output by 11.6 g/L. In comparison to batch fermentation (24.8 g PDO/L; 0.58 mol PDO/mol glycerol) there was 2.8-fold improvement with fed-batch process resulting in accumulation of 70.1 g PDO/L (Yield = 0.65 mol PDO/mol glycerol) using the studied biocatalyst in 150 h. In order to predict yields under different operational conditions a multiple linear regression model was developed (r 2  = 0.783) with six independent variables (p < 0.05), where biomass (g/L) and temperature ( o C) were forecasted as top contributors to PDO yield. Finally, this biocatalyst appears as a potential candidate for industrial use due to its non-pathogenic nature, ability to grow in wide pH and temperature conditions, tolerance to high substrate and product concentration, insignificant generation of by-products and Coenzyme B12 independent biotransformation. The study can add value to bio-utilization of RCG to produce green 1, 3-propanediol. Graphical abstract: Image 1 Highlights: A new 1, 3-propanediol producer namely, Clostridium butyricum L4 was isolated. Shake flask optimization for fermentative reforming of glycerol using isolate. Fed-batch process development resulting in production of 70.1 g PDO/L. Multiple linear regression (MLR) model was developed. Highest contributors revealed by MLR t -test are biomass (g/L) and temperature ( o C).